Facebook as a Learning Support Tool for NSSCO Physical Science Grade 12 Learners in Selected schools in the Oshikoto Region, Namibia - Boer, Perien; Amunime, Leonard; Haipinge, Erkkie (Namibian Journal for Research, Science and Technology, 2022)
The use of Facebook in Namibia is focussed on maintaining contact with friends and relatives, conduct sales on Marketplace, and to get updates on daily news (Peters, Winchiers-Theophilus & Mennecke, 2015). The purpose of the study was to explore whether Facebook has the potential to support learning and mastery of Physical Science content to improve learners’ academic performance on the topic of stoichiometry at Grade 12 level in selected schools in the Oshikoto Region. Study hypothesis is: H0 – There is no significant difference in the learners’ academic performance in NSSCO Physical Science on the topic of stoichiometry when Facebook is used as a learning support tool. H1 – There is a significant difference in the learners’ academic performance in NSSCO Physical Science on the topic of stoichiometry when Facebook is used as a learning support tool. The study used a quantitative approach with a quasi-experimental design, constituted of a Non- Equivalent-Groups Pre-test, Intervention and Post-test. The results show there exists a significant difference between the control and experimental score marks when Facebook was used as a learning support tools. The relevance of this study shows that teachers should learn to embrace using Facebook to support learning.